ATOMS: ALMA Three-millimeter Observations of Massive Star-forming regions – XV. Steady accretion from global collapse to core feeding in massive hub-filament system SDC335. Issue 3 (17th February 2023) - Xu, Feng-Wei; Wang, Ke; Liu, Tie; Goldsmith, Paul F; Zhang, Qizhou; Juvela, Mika; Liu, Hong-Li; Qin, Sheng-Li; Li, Guang-Xing; Tej, Anandmayee; Garay, Guido; Bronfman, Leonardo; et al.
ABSTRACT: We present ALMA Band-3/7 observations towards 'the Heart' of a massive hub-filament system (HFS) SDC335, to investigate its fragmentation and accretion. At a resolution of ∼0.03 pc, 3 mm continuum emission resolves two massive dense cores MM1 and MM2, with $383(^{\scriptscriptstyle +234}_{\scriptscriptstyle -120})$   M ⊙  (10–24 % mass of 'the Heart') and $74(^{\scriptscriptstyle +47}_{\scriptscriptstyle -24})$   M ⊙, respectively. With a resolution down to 0.01 pc, 0.87 mm continuum emission shows MM1 further fragments into six condensations and multi-transition lines of H2 CS provide temperature estimation. The relation between separation and mass of condensations at a scale of 0.01 pc favors turbulent Jeans fragmentation where the turbulence seems to be scale-free rather than scale-dependent. We use the H 13 CO +   J  = 1 − 0 emission line to resolve the complex gas motion inside 'the Heart' in position-position-velocity space. We identify four major gas streams connected to large-scale filaments, inheriting the anti-clockwise spiral pattern. Along these streams, gas feeds the central massive core MM1. Assuming an inclination angle of 45(± 15)° and a H 13 CO +  abundance of 5(± 3) × 10 −11, the total mass infall rate is estimated to be 2.40(± 0.78) × 10 −3   M ⊙  yr −1, numerically consistent with the accretion rates derived from the clump-scale spherical infall model and the core-scale outflows. The consistency suggests a continuous, near steady-state, and efficient accretion from global collapse, therefore ensuring core feeding. Our comprehensive study of SDC335 showcases the detailed gas kinematics in a prototypical massive infalling clump, and calls for further systematic and statistical studies in a large sample.